The impact of post-procedural complications on reimbursement, length of stay and mechanical ventilation among patients undergoing transcatheter aortic valve implantation in Germany - Kaier, Klaus; Frankenstein, Lutz (The European journal of health economics, 2018)
Background: The impact of various post-procedural complications after transcatheter aortic valve implantation (TAVI) on resource use and their consequences in the German reimbursement system has still not been properly quantified. Methods: In a retrospective observational study, we use data from the German DRG statistic on patient characteristics and in-hospital outcomes of all isolated TAVI procedures in 2013 (N = 9147). The impact of post-procedural complications on reimbursement, length of stay and mechanical ventilation was analyzed using both unadjusted and risk-adjusted linear and logistic regression analyses. Results: A total of 235 (2.57%) strokes, 583 (6.37%) bleeding events, 474 (5.18%) cases of acute kidney injury and 1428 (15.61%) pacemaker implantations were documented. The predicted reimbursement of an uncomplicated TAVI procedure was €33,272, and bleeding events were associated with highest additional reimbursement (€12,839, p < 0.001), extra length of stay (14.58 days, p < 0.001), and increased likelihood of mechanical ventilation for more than 48 h (OR 17.91, p < 0.001). A more moderate complication-related impact on resource use and reimbursement was found for acute kidney injury (additional reimbursement: €5963, p < 0.001; extra length of stay: 7.92 days, p < 0.001; ventilation >48 h: OR 6.93, p < 0.001) as well as for stroke (additional reimbursement: €4125, p < 0.001; extra length of stay: 4.68 days, p < 0.001; ventilation >48 h: OR 5.73, p < 0.001). Pacemaker implantations, in contrast, were associated with comparably small increases in reimbursement (€662, p = 0.006) and length of stay (3.54 days, p = 0.006) and no impaired likelihood of mechanical ventilation more than 48 h (OR 1.22, p = 0.156). Interestingly, these complication-related consequences remain mostly unchanged after baseline risk-adjustment. Conclusions: Post procedural complications such as bleeding events, acute kidney injuries and strokes are associated with increased resource use and substantial amounts of additional reimbursement in Germany, which has important implications for decision making outside of the usual clinical sphere.